Overcoming Reductionism. On „In-depth” Systems Analysis in the Political Science of Religion - Michał Gierycz (Chrześcijaństwo-Świat-Polityka)
The starting point of the article is the observation made by Ernst Wolfgang Böckenförde, according to which political science perceives itself as an „atheistic science in its proper sense” and documents problematic consequences of this paradigm on the grounds of „political science of religion” (such as, for example, reducing religion to ideology and Churches to groups of interests). In this context the author poses a question whether the theory and the instrumentarium of the political science creates possibilities of non-reduction approach to religion. The article provides an answer to this question. In the first part, outlining changes in the understanding of political science, the author proves that political science, in its theoretical and methodological body leaves some space for what we currently define as „political science of religion”, as well as reveals the sources of special importance of the system paradigm for political research. The second part brings the analysis of the current interpretation of this paradigm and shows their role in consolidating the „religious cataract” of political science. In the third part, referring to Easton’s writing, the author presents the theoretical possibilities of „deepening” the system analysis as well as examples of research techniques and approaches, allowing us to analyze the role of religion in political processes in a non-reduction way. The article proves therefore that it is possible to analyze religion as a social phenomenon differring from politics not only from the theoretical, but also from methodologicsl perspective (the so-called in-depth system analysis).